Effect of Dietary Incorporation of Yellow Mealworm as a Partial Fishmeal Replacer on Growth, Metabolism, and Intestinal Histomorphology in Juvenile Meagre (Argyrosomus regius) - Saavedra, Margarida (2023)
Publisher Copyright: © 2023 Margarida Saavedra et al. This study was supported by the National Project DIVERSIAQUA II (MAR-02.01.01 FEAMP-0175) and by the project ATLAZUL–Impulsionar a Aliança Litoral Atlântica para o Crescimento Azul (0755_ATLAZUL_6_E) from Spain-Portugal Interreg (POCTEP).